2019
DOI: 10.3390/ani9070395
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Heat Stress Induces Acute Phase Responses and Serum Metabolome Changes in Finishing Pigs

Abstract: Heat stress (HS) is a main environmental challenge affecting the animal welfare and production efficiency in pig industry. In recent years, numerous reports have studied the alterations in gene expressions and protein profiles in heat-stressed pigs. However, the use of metabolome to unravel adaptive mechanisms of finishing pig in response to chronic HS have not yet been elucidated. We aimed to investigate the effects of chronic HS on serum metabolome in finishing pigs, and to identify the biomarkers of heat st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…In several in vivo studies where the global heat stress was evaluated in different matrices (serum, plasma, urine, milk, liver), alterations in the amino acid metabolism, TCA cycle, and nucleotide metabolism were also found [28,29,30]. Our findings are in agreement with the changes found in in vivo studies, thereby suggesting translatability of our results.…”
Section: Discussionsupporting
confidence: 91%
“…In several in vivo studies where the global heat stress was evaluated in different matrices (serum, plasma, urine, milk, liver), alterations in the amino acid metabolism, TCA cycle, and nucleotide metabolism were also found [28,29,30]. Our findings are in agreement with the changes found in in vivo studies, thereby suggesting translatability of our results.…”
Section: Discussionsupporting
confidence: 91%
“…Increased evidences have suggested that the interactions between host and intestinal microbiota take part in nutrient metabolism, immune homeostasis and pathogenic bacteria resistance in mammals (Leser and Molbak ; Hooper et al ). HS leads metabolic and immune disorders through whole‐body thermoregulation (Sohail et al ; Cui et al ). However, the possible roles of intestinal micro‐organisms had always been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Pigs are particularly vulnerable due to their lack of functional sweat glands, and the thick layer of subcutaneous adipose tissue that they possess which impedes effective radiant heat loss [42]. Heat stress triggers an adaptive stress response by regulating a complex array of genes and metabolites [16,18,21]. In this study we found significant differences in water and feed intake post heat stress, and a significant difference in water intake post heat stress treatment between male and female pigs (Table S1).…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, a variety of metabolites involved in carbohydrate, amino acid, fatty acid and amine metabolism are modulated, including glucose, lactate, alanine, cysteine, isoleucine, etc. [20][21][22][23]. However, these studies did not involve integrated transcriptome and metabolome profiling, which could lead to better understanding of the effect of heat stress on swine physiology, gene expression and metabolism, which will help in designing and implementing innovative strategies to limit the economic losses due to heat stress on pig farm profitability.…”
Section: Introductionmentioning
confidence: 99%